Analisis Stress Kerja, Motivasi, Disiplin Kerja, Dan Kepemimpinan Transformasional Terhadap Kinerja Pegawaiâ (Studi Kasus Perum LPPNPI Airnav Indonesia Cabang Pratama Semarang) - Sayfu Niafah, 14.05.51.0209; Indriyaningrum, Kis (Students Journal of Economic and Management, 2018)
The purpose of this study is to determine the effect of Work Stress, Motivation, Work Discipline, and Transformational Leadership On Performance Employees At Perum LPPNPI (Airnav Indonesia) Branch Pratama Semarang. This research uses qualitative research, with the employee population is 85 employees. Data collection using questionnaires with Likert scale. The research uses sampling The result showed that the Work Stress not affect on Employee Performance, Motivation not effect on Employee Performance, Work Discipline has a positive and significant impact on Employee Performance, and Transformational Leadership has a positive and significant impact on Employee Performance, and Employee Performance. From resul tresearch showed Transformational Leadership very strong and effect can explain the variable employee performance.Keywords: Work Stress, Motivation, Work Discipline, Transformational Leadership and Employee Performance